Editorial: slow progress to optimising H. pylori eradication treatment with antisecretory drugs. Issue 6 (22nd August 2022) - Gisbert, Javier P.; Hunt, Richard H.
Abstract : LINKED CONTENT This article is linked to Ang et al papers. To view these articles, visit https://doi.org/10.1111/apt.17070 and https://doi.org/10.1111/apt.17167